Improvement of Faculty’s Skills on the Creation of Items for Progress Testing Through Feedback to Item Writers: a Successful Experience - Hamamoto Filho,Pedro Tadao (2020)
Abstract: The evaluation of knowledge is an important step in the teachers’ work, because it is fundamental that the evaluation results be valid and reliable. Several faculty development programs have been undertaken to improve teachers’ skills on item writing. Few studies, however, have explored the benefits of providing feedback to multiple-choice item writers. Progress Testing is a longitudinal assessment of students’ knowledge gain. Their results are useful for generating feedback to students, teachers and medical school managers. The aim of this report is to present a successful experience of faculty development on high-quality item writing for Progress Testing through feedback about the fate of the items written by faculty members. Annually, faculties from medical schools participating in a consortium for the application of the Progress Test are asked to formulate new items to compose the test version. However, the fate of the items is not known by their authors, that is, they do not know if the items are incorporated into the test, if the items have good quality, what is the students’ performance in each of the items, and what is the psychometric function of the items. In 2017, one of the schools participating in the consortium offered its item authors a feedback regarding the flaws in item writing, modification of items by the review committee and students’ performance, as well as psychometric function in each item. The percentage of flawed item (items without enough quality to be selected for the test) was more than 30%. There was an inverse relation between the number of flawed item and the number of items included in the final exam, when analyzing the different content areas of the test (that is, Internal Medicine, Surgery, Pediatrics, Obstetrics and Gynecology, Public Health, and Basic Sciences). In the following year, we observed a decrease in the number of flawed item (less than 10%) and an increase in the number of eligible items to be selected for the Progress Testing. Therefore, giving feedback to item writers seems to be a good strategy for developing the faculty’s ability on writing good quality items.